Doses e fontes alternativas de nitrogênio no milho sob plantio direto em solo arenoso - Soratto, Rogério Peres [UNESP]; da Silva, Ângela Honório; Cardoso, Susiane de Moura [UNESP]; de Mendonça, Cristiane Gonçalves (FapUNIFESP (SciELO), 2011)
The objective of this work was to evaluate the effect of nitrogen sources and rates on maize nutrition and grain yield under no-tillage system in sandy soil. The experiment was conducted in a Typic Quartzipsamment, in the city of Cassilândia, State of Mato Grosso do Sul, Brazil. A completely randomized block design was used in a factorial array 3x4 with four replicates. Treatments consisted of three sources [urea, extruded urea with starch (Starea), and ammonium sulfonitrate with nitrification inhibitor of 3,4-dimethylpyrazole-phosphate (Entec® 26)] and four rates (0, 45, 90 and 180 kg ha-1) of nitrogen, applied in side-dressing when the plants presented four and six expanded leaves. The nitrogen source affected N, K, and S concentration in the leaf, but did not interfere in the components of production and maize grain yield. Nitrogen application like ammonium sulfonitrate promoted higher concentrations of N, K and S in the maize leaf in relation to the urea, especially in the larger rates studied. Side-dressing nitrogen fertilization increased the number of ears per plant, number of grains per ear and grain yield, grown under no-tillage system in sandy soil, independent of the used source.
Rates and alternative sources of nitrogen fertilization on maize under no-tillage in sandy soil
Keywords: Dimethylpyrazole-phosphate; Extruded urea; Nitrogen fertilization; Sulfonitrate; Urea; Zea mays L.